1987
DOI: 10.1007/bf00542189
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cimetidine versus ranitidine on doxepin pharmacokinetics

Abstract: The effect of cimetidine and ranitidine on doxepin pharmacokinetics was studied in 6 healthy volunteers. Each subject completed 3 study phases: Treatment A, 9 consecutive doses of 50 mg doxepin (once daily); Treatment B, same as Treatment A but co-administration of cimetidine 600 mg b.i.d. starting after the sixth doxepin dose and continuing until approximately 2 days following discontinuation of doxepin administration; Treatment C, identical to Treatment B but with ranitidine 150 mg b.i.d. instead of cimetidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…No significant changes in imipramine, amitriptyline or doxepin pharmacokinetics were shown in studies with healthy volunteers following ranitidine pretreatment or with simultaneous administration (Curry et al 1987;Kurowski & Reim 1986;Sutherland et al 1987;Wells et al 1986). Experimental studies performed in vitro with human liver microsomes showed that imipramine demethylation or demethyl-imipramine hydroxylation were not changed (Spina & Koike 1986).…”
Section: Antidepressantsmentioning
confidence: 89%
“…No significant changes in imipramine, amitriptyline or doxepin pharmacokinetics were shown in studies with healthy volunteers following ranitidine pretreatment or with simultaneous administration (Curry et al 1987;Kurowski & Reim 1986;Sutherland et al 1987;Wells et al 1986). Experimental studies performed in vitro with human liver microsomes showed that imipramine demethylation or demethyl-imipramine hydroxylation were not changed (Spina & Koike 1986).…”
Section: Antidepressantsmentioning
confidence: 89%